The impact of e-learning towards students academic performance / Nur Hazimah Mohamed Hazim - Mohamed Hazim, Nur Hazimah (Faculty of Business and Management, 2013)
This research conducts to study about the Impact of E-Learning towards Student Academic Performance at Multimedia University (MMU) Bukit Beruang, Melaka. E-Learning has become a new trend of learning style that replaces the traditional classroom style. As we informed, nowadays, most of the students monopolized the tertiary education institution are consist of the Gen Y-er, whom born from the year 1982 to 2000, that mostly "digital natives", in which they are readily computer literate, familiar with high-technological environment. Therefore this Oen Y-er is known for not having any problems closely related with computer operating system. We are conducting this study to determine the E-Learning factors that impact towards students' academic performance. There are two objectives of this study which is to identify the level of student academic performance, and to determine the relationship between E-Leaming factors and student academic performance. The data that use in our study is primary data. The data collection we use is survey. The survey will be selfadministered and in a form of questionnaire. The questionnaire consists of 1 to 5 response Likert scale. The expected finding of this study is student academic perfonnance was positively impacted by E-Leaming through Perceived Ease of Use, Perceived Usefulness, Computer Anxiety, and Computer Self-Efficacy.